From Health Crisis to Financial Distress - Reinhart, Carmen M. (World Bank, Washington, DC, 2021)
I discuss the multifaceted economic and financial vulnerabilities that have been created or exacerbated by the COVID-19 pandemic on a foundation of already weak economic fundamentals in many countries. Crises often do not travel alone. Banking, sovereign debt, exchange rate crashes, sudden stops, and inflation often intersect to become severe conglomerate crises. Historically, whether of the individual or conglomerate variety, crises influence the shape and speed of economic recovery. As the health crisis morphs into a financial or debt crisis in some countries, I discuss what may lie ahead in terms of the stages in crisis resolution and a brief reflection on how the resolution process can be expedited.